Efeito da suplementação de probiótico nas alterações imunometabólicas, antropométricas e de qualidade do sono em indivíduos com apneia obstrutiva do sono (AOS) - Santos, Luiz Gustavo dos (2023)
Obstructive sleep apnea (OSA) is a condition that can disrupt airflow leading to hypoxia and hypercapnia. This condition triggers comorbidities such as hyperlipidemia, insulin resistance, diabetes, and increased intestinal permeability. Currently, it affects about 98 million Brazilians, with Countinous Airway Pressure (CPAP) as the gold standard treatment. However, it has limitations. Because of this, this study aimed to evaluate the impact of Lactococcus lactis (LLa61) supplementation on anthropometric, body composition, immunometabolic, quality of life, sleep, and daytime sleepiness parameters in individuals with OSA using CPAP. Therefore, 25 individuals, adults, of both genders, using CPAP were selected to participate in the study. This work is a prospective, randomized, double-blind, placebo-controlled clinical trial in two stages of 12 weeks each. The Probiotic Group received the microorganism Lactococcus lactis (LLa61) at a concentration of 2x109.1 CFU while the placebo group received the inert cellulose excipient. The study was approved by the UFLA Research Ethics Committee (4,383,855) and by the Brazilian Clinical Trials Registry platform (RBR-9f4f5dc). Before and after the intervention period, the following estimates were made: anthropometric, body composition, and biochemical, in addition to subjective estimates: food consumption, quality of life, quality of sleep, and sleepiness. As a result, there were no significant changes due to the effect of probiotic supplementation on anthropometric estimates (ANT) and body composition (CP), quality of life (QL), sleep (QS), as well as laboratory variables (LAB), however, it was possible to identify changes in the eating habits of the participants, with an increase in caloric intake, proteins, and vitamins niacin and riboflavin only in the group supplemented with probiotics at the end of the VET intervention (GPro TI=1,554.02Kcal/ TII=1,683.40Kcal vs GPla TI =1,522.31Kcal/ TII=1,380.90Kcal) (p=0.014); PTN (GPro TI=69.94g/ TII=77.65g vs GPla TI=67.84g/ TII=58.61g) (p=0.017); Total fat (GPro TI=54.12g/ TII=56.66g vs GPla TI=56.05g/ TII 45.68g) (p=0.009); Riboflavin (GPro TI=0.85mg/ TII=0.49mg vs GPla TI=1.07mg/ TII=0.40mg) (p=0.019) and Niacin (GPro TI=15.89mg/ TII=19mg vs GPla TI= 14.08mg/ TII=10.48mg) (p=0.017). No changes were observed due to the effect of supplementation on quality of life and sleep, however, a lower sleep latency can be observed for the GPro (TI=39.20min±56.80/ TII=26.50min±23.88) vs GPla (40.50min±62.57/ TII=33.50min±17.13) (p=0.072). Finally, biochemical analyzes also did not show significant differences for the proposed intervention. Conclusion: Supplementation with a probiotic strain of Lactococcus lactis (LLa61) was not effective in modulating immunometabolic, anthropometric, quality of life, and sleep parameters in individuals with OSA undergoing CPAP treatment. However, further investigations in humans are needed to look for specific inflammatory markers, as well as mucosal integrity, to guarantee the result observed in the present study.